A tool to evaluate physiotherapy clinical education in South Africa. - Naidoo, Vaneshveri; Stewart, Aimée V.; Maleka, Morake E.D. (South African Journal of Physiotherapy, 2022)
Background: Physiotherapy clinical education is complex. The dynamic learning milieu is fluid and multidimensional, which contributes to the complexity of the clinical learning experience. Consequently, there are numerous factors which impact the clinical learning experience which cannot be measured objectively – a gap which led to the development of our study. Objectives: To develop, validate, and test the reliability of an assessment tool that evaluates the effectiveness and quality of physiotherapy clinical education programmes. Method: A mixed methods approach in three phases included physiotherapy academics, clinical educators, and clinicians throughout South Africa. Phase One was a qualitative study: focus group discussions determined items and domains of the tool. Phase Two established the content and construct validity of the tool, a scoring system and a name for the tool, using the Delphi method. In Phase Three, factor analysis reduced the number of items, and the feasibility and utility of the tool was determined cross-sectionally. Results: The Vaneshveri Naidoo Clinical Programme Evaluation Tool (VN-CPET) of 58 items and six domains was developed and found to be valid, reliable (α = 0.75) and useful. The six domains of VN-CPET include governance; academic processes; learning exposure; clinical orientation; clinical supervision and quality assurance and monitoring and evaluation. Conclusion: The Vaneshveri Naidoo Clinical Programme Evaluation Tool is a valid, reliable and standardised tool, that evaluates the quality and effectiveness of physiotherapy clinical education programmes. Clinical implications: This tool can objectively evaluate the quality and effectiveness of physiotherapy clinical education programmes in South Africa, and other health science education programmes, both locally and globally, with minor modification.